Human Capital Plan Analysis in Improving Competitiveness and Productivity at FranchiseGlobal.com - Bakir Bakir; Edi Hamdi; Rhian Indradewa; Ferryal Abadi (Publikasi Indonesia, 2024)
This research aims to analyze the Human Capital Plan strategy implemented by FranchiseGlobal.com to increase the competitiveness and productivity of the company. This research collects data through interviews, documentation, and direct observation using a qualitative descriptive approach. This study also evaluates the implementation of McKinsey's 7S Framework in the Human Capital strategy at FranchiseGlobal.com. The results showed that FranchiseGlobal.com has implemented a strategy divided into short, medium, and long term to improve recruitment, employee development, and talent retention. Although the company has made progress in HR management, there are still challenges in building an inclusive corporate culture and integrating new technologies in the HR management process. This research concludes that the Human Capital Plan implemented at FranchiseGlobal.com effectively supports company growth but requires improvement in technology and cultural inclusion.